A novel time-saving multiplex PCR assay for detecting and discriminating the most common canine Babesia species in Europe. (May 2023) - Remesar, S.; Méndez, A.; Benito, A.; Prieto, A.; García-Dios, D.; López, C.M.; Panadero, R.; Díez-Baños, P.; Morrondo, P.; Díaz, P.
Abstract: In Europe, most cases of canine babesiosis are caused by Babesia canis, Babesia vogeli (large piroplasms) and Babesia vulpes (small piroplasm). Molecular diagnosis is recommended due to its high sensitivity. Species identification after sequencing allows applying a rapid and efficient treatment, leading to a better prognosis; however, it is expensive and time-consuming. Thus, the objective of the present study was to develop a time-saving multiplex polymerase chain reaction (PCR) for simultaneously detecting and discriminating between large and small forms without sequence analysis. A new multiplex PCR was designed and tested using blood samples from 79 dogs showing clinical signs compatible with babesiosis which were previously analysed using blood smears and molecular methods. Multiplex PCR successfully discriminated between both Babesia groups showing bands of 700 and 890 bp for B. canis / B. vogeli and B. vulpes, respectively. No significant differences in the results of both PCR were detected and a substantial agreement between protocols (κ = 0.64) was found. Our multiplex PCR represents a reliable tool for detecting infections by the major Babesia spp. in dogs from Europe. Since no sequence analysis is required for identifying the species involved, this PCR allows the rapid administration of an appropriate treatment, thus improving the survival rate of the infected animals. In addition, it will represent a helpful tool for unravelling the real prevalence and distribution of B. vulpes and its implication in clinical cases. Highlights: Multiplex PCR is a time-effective tool for diagnosing canine babesiosis in Europe. It allows differentiating infections caused by large and small Babesia spp. This tool is useful to clarify the involvement of B. vulpes in clinical cases.